Predicting Mathematics Achievement in Secondary Education: The Role of Cognitive, Motivational, and Emotional Variables - Abín, Amanda; Núñez, José Carlos; Rodríguez, Celestino; Cueli, Marisol; García, Trinidad; Rosário, Pedro (Frontiers in Psychology, 2020)
Academic achievement in general, and in mathematics in particular, is positively associated not only with cognitive abilities, but also with emotional and motivational skills. The objective of this study was to analyze the prediction strength of cognitive, motivational, and emotional variables in mathematics achievement throughout high school, considering students’ gender and age. A large sample of 2,365 Spanish students from the 4 years of high school (12–16 years old) participated in the study. Students provided information about their intellectual skills, perceived competence in mathematics, perceived utility of mathematics, intrinsic interest in learning, mathematics anxiety, and their causal attributions (for failure and for success), and of their achievement in mathematics. Data showed differences according to gender and the school grade level. The motivational and affective variables did not seem to play an important role in this relationship as predicted in the current study. The results of this study are discussed in light of previous research.